2015
DOI: 10.1080/07900627.2015.1033514
|View full text |Cite
|
Sign up to set email alerts
|

Farmers' responses to climate change impact on water availability: insights from the Indrawati Basin in Nepal

Abstract: There is a need to assess the potential impacts of climate change on agriculture in order to plan appropriate adaptation measures. Farmers are already adapting to these changes to a certain degree. This article presents a case study of rainfed and farmer-managed irrigated agriculture in the Indrawati Basin, Nepal. It describes farmers' perceptions of climate change, an analysis of historical water availability, and future projections of temperature and precipitation. Adaptation strategies already being used by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 13 publications
(13 reference statements)
5
21
1
Order By: Relevance
“…However, irrigated land has increased in Sindhupalchok (CBS 2010), including in the Melamchi Valley, where nearly 27% of respondents reported scarcity of water in the irrigation canals. This finding concurs with Sijapati and Bhatt (2012) and Pradhan et al (2015), who reported a decline in water supplies in recent years in the Melamchi Valley. Water scarcity can also be due in part to poorly maintained irrigation systems.…”
Section: Major Climate-related Hazards and Their Impacts On Livelihoosupporting
confidence: 95%
“…However, irrigated land has increased in Sindhupalchok (CBS 2010), including in the Melamchi Valley, where nearly 27% of respondents reported scarcity of water in the irrigation canals. This finding concurs with Sijapati and Bhatt (2012) and Pradhan et al (2015), who reported a decline in water supplies in recent years in the Melamchi Valley. Water scarcity can also be due in part to poorly maintained irrigation systems.…”
Section: Major Climate-related Hazards and Their Impacts On Livelihoosupporting
confidence: 95%
“…Farmers did not accurately perceive or were uncertain about future rainfall patterns and, actually, the rainfall scenarios do not provide a clear trend during the irrigation season, especially since most farming activities are irrigated in the study area. Their perceptions of rainfall differed to those of farmers reported in other studies (e.g., [50,51]) whose farming mainly relies on rain water, in which farming calendars/practices are to be adjusted to better cope with perceived changes in rainfall. In addition, farmers remembered more "unexpected events" [15,24] and production losses in the most recent years [52,53], often confusing weather with climate [15].…”
Section: Symmetries and Asymmetries Between Farmers' Perceptions And contrasting
confidence: 67%
“…Some farmers have already abandoned some of their important traditional crops like rice, pulses, different cereal crops, tuber, and sweet potato-and have even abandoned agriculture on their land, which ends up becoming fallow. They cited that the lack of sufficient water, crop-specific diseases, low production, inadequate benefits, and unfavorable climate were the major reasons in this decision [7].…”
Section: Agricultural Impactsmentioning
confidence: 99%